The Possibility of Hyaluronic Acid as a Theraupetic Option for Peyronie's Disease: Systematic Review - Pradipta Mahardika Wijaya, Putu Gede; Thede Surya Putra, I Gusti Agung (Green Publisher Indonesia, 2024)
Peyronie's disease (PD) is a progressive, non-malignant disorder affecting the penile connective tissue, characterized by fibrous plaque formation leading to penile curvature and functional impairment. This study aimed to evaluate the effectiveness of hyaluronic acid (HA) as a therapeutic option for PD. A systematic review was conducted following PRISMA guidelines and utilizing the PICOT framework. Articles were sourced from PubMed, ScienceDirect, ProQuest, Wiley, and Google Scholar, focusing on studies published between 2012 and 2022 in English and with full-text availability. Six studies were analyzed, including cohort studies and clinical trials. The findings revealed that intralesional HA injections significantly reduced plaque size, improved penile curvature, and enhanced erectile function, as measured by the International Index of Erectile Function (IIEF). HA's anti-inflammatory and antioxidant properties, along with its ability to remodel collagen, contributed to these outcomes. Compared to other treatments, such as verapamil, HA demonstrated superior efficacy with minimal side effects. The discussion highlights HA's potential as a non-surgical treatment that addresses both physical symptoms and improves patient satisfaction. In conclusion, HA offers a promising, effective, and safe therapeutic alternative for PD, addressing critical gaps in the current management of the disease.